Evaluation of the Reliability of Transport Service of Logistics Chains - Vojtov, Viktor; Berezchnaja, Natalija; Kravcov, Andrey; Volkova, Tetiana (International Journal of Engineering and Technology, 2018)
The article presents the analysis of approaches connected with solving the problems of increasing the effectiveness of managing the processes of goods movement in the supply chains. The attention has been focused on estimating the qualitative component of transport services, and that is the reliability index. The approaches focused on improving the efficiency of providing transport services have been studied. The main parameters influencing the reliability of transport and logistics services are identified: time, qualitative and quantitative characteristics of the goods, as well as the financial component – the cost of the provided transport service. A new methodical approach to estimating the reliability of goods flows in the supply chains is proposed. It is based on the main principles of the theory of automatic regulation and the determination of the reliability of technical systems. A complex index of reliability of transport services of logistics chains is offered: the readiness coefficient and the technical use coefficient. On the basis of structural and parametric identification of the dynamic model of the logistic system of goods transportation, the considered approach allows identifying a large number of constructive and technological parameters which affect the movement of goods flows in the supply chains. The results of the simulation allow one to analyze the influence of the time constant  which characterizes the response time of the links in the transport and logistics system, that is, the ability of the transport service participant not to respond to any external influences, and the influence of the time constant  which is responsible for delays, non-productive time losses occurring during the delivery of the goods, on the dynamics of the transitional processes of the goods flow movement for each link in the supply chains. The elaborated method allows developing managing actions aimed at improving the quality of transport services.
Keywords: reliability; transport services; logistics system; supply chain; cargo flow.